The potential beneficial effect of exenatide on cisplatin induced nephrotoxicity in non-diabetic rats - Abdel-Mohsen Abdel-Aziz, Eman; M. Abo El Wafa, Sahar (International Journal of Pharmacology and Toxicology, 2020)
Background: Cisplatin is a major antitumor drug used for treatment of solid tumors. Nephrotoxicity is its main limiting side effect. Exenatide is described as an incretin mimetic polypeptide, it acts as a GLP-1 receptor agonist and its insulinotropic activity is mediated through binding to and stimulation of GLP-1 receptors on human pancreatic Î²-cells. Aim: the present work was designed to study the effect of exenatide on experimentally cisplatin induced nephropathy in non- diabetic rats. Materials and Methods: Thirty two male adult Sprague Dawley rats randomly divided into four groups, each consisted of 8 animals, and distributed as follows: Group I: (control) normal group and received saline vehicle. Group II: (cisplatin) group includes rats injected intraperitoneally by a single dose of cisplatin (6 mg/kg) to induce nephrotoxicity, received no treatment and were sacrificed 7 days after cisplatin administration. Group III: (exenatide) group: rats treated by exenatide (10 mg/kg/day s.c.) for 4 weeks. Group IV: (exenatide+cisplatin) group: rats treated by exenatide (10 mg/kg/day s.c.) for 4 weeks before induction of nephrotoxicity by cisplatin. The following parameters were measured: fasting blood glucose, serum urea, serum creatinine, reduced glutathion (GSH) level in the renal tissue, tumor necrosis factor-Î± (TNF-Î±) level in the renal tissue, renal blood flow changes and histopathological changes of the kidney. Results: Pretreatment with exenatide resulted in significant reduction in serum urea, serum creatinine level and renal TNF- Î± level compared to cisplatin group but still significantly higher than control group with significant increase in renal GSH level and renal blood flow compared to cisplatin group but still also significantly lower than control group. Cisplatin group showing tubular degeneration with infiltration of inflammatory cells while pretreatment with exenatide showing certain improvement in general histological structure with mild tubular degeneration and less inflammatory cell infiltration. Conclusion: it can be concluded that the use of exenatide improved the biochemical and histopathological changes that occur in the renal tissue by cisplatin.Â Â